Implementation of the Phoenix Sepsis Score in Vietnamese Pediatric Patients: Prognostic Accuracy and Comparative Analysis with Neutrophil- Lymphocyte Ratio - Chau Duc Nguyen-Huu; Bich-Ngoc Phan; Van-Tuy Nguyen (Güncel Pediatri, 2024)
Introduction: To evaluate the implementation of the Phoenix sepsis score in the prognosis of pediatric sepsis, and to compare the prognostic accuracy of the Phoenix with that of the NLR. Materials and Methods: A retrospective cohort analysis was conducted on pediatric patients diagnosed with sepsis. Patients were categorized using the Phoenix and the NLR. Results: In a cohort of 63 pediatric patients diagnosed with sepsis using established criteria, the Phoenix sepsis score identified 16 as suspected sepsis and 47 as confirmed sepsis. Patients with confirmed sepsis exhibited significantly different clinical and laboratory features, such as pre-existing conditions, lower Glasgow Coma Scale scores, lymphopenia, and lactic acidosis (p < 0.05). The Phoenix demonstrated superior prognostic accuracy in predicting mortality compared to the NLR, with an AUC of 0.886 versus 0.649. Conclusion: The Phoenix sepsis score is a valuable prognostic tool in pediatric sepsis, outperforming NLR in predicting mortality.